Analysis of Raw Material Control Using the EOQ Method in the Suwar-Suwir Agro-Industrial Business UD Sari Rasa, Jember - Anggraeni, Revani Devita; Kustiari, Tanti; Muksin (Politeknik Negeri Jember, 2024)
Suwar-suwir UD Sari Rasa is an agroindustry business located at Jalan Trunojoyo No. 91, Kauman, Kepatihan, Kaliwates District, Jember Regency, East Java. This business produces shredded sweets made from cassava tape as raw material. Suwar-suwir has a variety of flavor variants consisting of vanilla, pineapple, strawberry, chocolate, and pandan flavors. The purpose of this study was to determine the optimal amount of cassava tape raw material inventory, which should be carried out by the UD Sari Rasa suwar-suwir business, when is the right time to reorder cassava tape raw materials, and what is the optimal total ordering cost to make cassava tape raw materials. procurement of raw materials for cassava tape. The method used in this study is EOQ (Economic Order Quantity), to determine the optimal quantity of raw material orders, ROP (Reorder Point) analysis tool to find out when is the right time to reorder raw materials, Safety Stock analysis tool is used to determine safety stock and Total Cost of Inventory (Total Cost) to calculate the total cost of ordering raw materials. Based on the results of the analysis using the EOQ method, the optimal number of orders for raw materials is 790 Kg of cassava tape with a purchase frequency of 63 times in one year with reordering of raw materials if the inventory reaches 305 Kg of cassava tape with a total inventory cost of Rp. 399.992,000.